IMPLEMENTATION OF THE PRIVATE PUBLIC PARTNERSHIP (PPP) POLICY IN THE SUPPLY OF DRINKING WATER IN TANGERANG DISTRICT - Slamet Setiawan (JPPM: Journal of Public Policy and Management, 2020)
This study describes the implementation of the Public Private Partnership (KPS) policy between the Tangerang Regency Government and PT. Aetra Air Tangerang in providing drinking water for the people of Tangerang Regency. This study aims to determine how the success of policy implementation using Edward III's theory as a measure of success. The key informant in this study is the Regional Secretary of Tangerang Regency as the person in charge and implementer of the policy. This research was conducted in a descriptive method with a qualitative approach. The data collection techniques in this study are by observation, interviews and desk study or literature study. The results of this study indicate that the implementation of the Public Private Partnership (KPS) policy between the Tangerang Regency Government and PT. Aetra Air Tangerang in the provision of drinking water, has been running quite well, especially in terms of resources, disposition and bureaucratic structure. problems and constraints are found in the communication factor where the transmission, clarity and consistency of policies have encountered many problems and it is necessary to find the most appropriate solution, so that policy implementation can be maximized and achieve policy objectives optimally.